A review of Islamic perspectives on leadership. (International Journal of Scientific Research and Management (IJSRM), 2019)
Islamic culture encourages and supports a rich and complete way of life, with guidance, both spiritual and secular, provided for every facet of the devotee’s life. The Qur’an and the Sunnah are the two sources for the Islamic concept of the role of the leader. The Qur’an is the holy book of the religion of Islam, and the Sunnah describes the exemplary life of Prophet Mohammad, largely understood through narration of his words and deeds – the Hadeeth. The Holy Qur’an is universally honoured by Muslims, who identify passages that are pertinent and influential to their lives. Leadership is a tenet that is highly emphasized in Islamic life and is embodied in the pillar of accountability. Indeed, the Prophet Mohammad in the Hadeeth states: ‘each of you is a guardian and is responsible for his subjects’ (Saheeh al Bukhari: 212). This form of multi-level leadership is highly encouraged in Islam. The operational principles that should be applied by Muslim leaders include the exercise of justice, fulfilment of trust, observance of righteousness, perseverance in doing what is right, and honouring promises (Beekum, 1999). The model of Islamic leadership has four dimensions: Consciousness of God, Competency, Consultation, and Consideration (The 4C model).